POSTOPERATIVE QUALITY OF RECOVERY AND ASSOCIATED FACTORS AMONG PEDIATRIC PATIENTS AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the postoperative quality of recovery using the Postoperative Quality of Recovery Scale (PostopQRS) and to analyze factors associated with postoperative recovery quality among pediatric patients at Nghe An Obstetrics and Pediatrics Hospital in 2025.Methods: This prospective descriptive study included 384 pediatric patients aged 6–15 years undergoing elective surgery at Nghe An Obstetrics and Pediatrics Hospital between December 1, 2024, and June 30, 2025. Data were collected from medical records and direct interviews using the PostopQRS tool at 15 min, 40 min, day 1 and day 3 postoperatively. Statistical analyses were performed using SPSS version 22.0, applying Chi-square tests and multivariate logistic regression to identify factors associated with postoperative recovery.Results: Most participants were aged 6-10 years (82.3%; mean age of 8.3 ± 2.3 years). 62.2% were male. Nutritional status showed 9.1% and 11.2% severe malnutrition. 78.6% received endotracheal anesthesia. Domain-level recovery at postoperative 40 minutes was 99.0% for physiological, 65.1% for nociception, 97.7% for emotion and 7.8% for cognition. Recovery of daily activities was observed in 18.5% and 23.7% on postoperative days 1 and 3, respectively. Full multidomain recovery was achieved in 5.2% on day 1 and 22.4% on day 3. No severe complications were reported. The satisfaction rate was 98.4%. Early pain recovery was significantly associated with age group, surgical invasiveness and preoperative anxiety level.Conclusions: The PostopQRS offers a comprehensive recovery assessment tool for pediatric patients. Overall recovery quality was favorable, though significantly associated with age, surgical type and preoperative psychological status. These findings advocate for implementing ERAS principles and developing tailored preoperative educational interventions for pediatric surgical patients.
Keywords: PostopQRS, recovery of consciousness.